MODIFIKASI SILIKA GEL DARI ABU SEKAM PADI DENGAN LIGAN DIFENILKARBAZON - I Wayan Sudiarta; Ni Putu Diantariani; Putu Suarya (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2013)
Modification of silica gel from rice husk ash by diphenylcarbazone ligand have been conducted. This study included synthesis of silica gel from rice husk ash, determination of the optimum ratio of ligand/silica gel, optimum time of silica gel modification The results showed that the modification of silica gel from rice husk ash with diphenylcarbazone has been successfully synthesized, indicated by appearearance of characteristic absorbances of Si-O-Si, Si-OH, -NH, Ar-H, C=O functional groups on the infra red spectra at 1096, 910-830, 3330, 3242, cm-1, and 1660 cm-1, respectively. The optimum of ligand/silica is 0,5 mmol : 0,5 g or 1mmol ligand 1g silica gel, with the modification time of 4 hours.